(untitled) (Nexo Revista Científica, 2021)
Micro-organisms are present in all environments and are capable of synthesizing products useful to man, they represent a few hundred species among the more than one hundred thousand described in nature. Biotechnology has an interdisciplinary character and through its tools, allows the production of products from raw materials, impacting their applications on food, agri-food industry, medicine, industrial production, environment and energy production, the use of micro-organisms being a constant in most areas. The importance of white biotechnology lies in the design of products and the application of biotechnological processes as an alternative to conventional chemical processes, which bring economic and environmental benefits and reduce or eliminate the use and generation of hazardous substances. The present work summarizes the research of several years developed in the PIENSA-UNI, with the purpose of collecting microorganisms from different sources, isolating them and identifying them by molecular way and finally to develop bioprocesses that contribute to the solution of environmental problems (bioremediation of heavy metals, soils, pesticides, petroleum, biolixiviation, industrial waste management), development of agricultural applications (growth stimulators, biofertilizers, bioinsecticides) and industrial as production of different enzymes.